Saved by their music. Gypsies in the 18th century Europe (Theatrum historiae, 2009)
The paper dedicated to the situation of the so called Gypsy people in the 18th century Europe concentrates on the relations between Gypsy and non Gypsy communities by presenting various, but predominantly negative, approaches towards these people. The paper is divided into four parts: (1) the beginning of academic interest in Gypsies, (2) the political situation of Hungarian and Spanish Gypsies in the 18th century, (3) social interactions between Gypsies and non Gypsies (gadje) illustrated by the Polish situation, (4) Gypsy music in the 18th century.
Keywords: (Spanish and Hungarian) Gypsy; 18th century Gypsy music; Anty Gypsyism